A Decision Tree for Donor Human Milk: An Example Tool to Protect, Promote, and Support Breastfeeding - Brandstetter, Shelley; Mansen, Kimberly; DeMarchis, Alessandra; Nguyen Quyhn, Nga; Engmann, Cyril; Israel-Ballard, Kiersten (Frontiers in Pediatrics, 2018)
Despite decades of breastfeeding promotion, exclusive breastfeeding rates for the first six months of life remain low, at around 40% globally. Those infants that are admitted to a neonatal ward are even less likely to be exclusively breastfed. Lactogenesis is frequently delayed in mothers that deliver early, with the added burden of separation of the unstable newborn and mother. For such vulnerable infants, donor human milk is recommended by the World Health Organization, UNICEF, and professional organizations as the next best alternative when mother’s own milk is unavailable and can serve as a bridge to full feeding with mother’s own milk. Hospital support of optimal breastfeeding practices is essential with thoughtful integration of donor human milk policies for those infants that need it most. We propose a decision tree for neonatal wards that are considering the use of donor human milk to ensure donor human milk is used to replace formula, not to replace mothers’ own milk. By first evaluating barriers to full feeding with mother’s own milk, healthcare workers are encouraged to systematically consider the appropriateness of donor human milk. This tool also seeks to prevent overuse of donor human milk, which has the potential to undermine successful lactation development. In settings where donor human milk supplies are limited, prioritization of infants by medical status is also needed. Readily available and easy to use tools are needed to support healthcare staff and mothers in order to improve lactation development and neonatal nutrition.